Vietnamese Communism In Comparative Perspective, 1st edition - Turley, William S. (Routledge, 2020)
This book focuses on how the Vietnam Communist party adapted to its environment in order to achieve and exercise power and to what degree these adaptations made the Vietnamese revolution distinctive.